A dithiacyclam-coordinated silver(i) polymer with anti-cancer stem cell activity. Issue 17 (23rd April 2021) - Johnson, Alice; Iffland, Linda; Singh, Kuldip; Apfel, Ulf-Peter; Suntharalingam, Kogularamanan
Abstract : A cancer stem cell (CSC) active, solution stable, silver(i ) polymeric complex bearing a dithiacyclam ligand is reported. Abstract : A cancer stem cell (CSC) active, solution stable, silver(i ) polymeric complex bearing a dithiacyclam ligand is reported. The complex displays similar potency towards CSCs to salinomycin in monolayer and three-dimensional cultures. Mechanistic studies suggest CSC death results from cytosol entry, an increase in intracellular reactive oxygen species, and caspase-dependent apoptosis.